The Language of Fear : Communicating Threat in Public Discourse - Cap, Piotr (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
'Cap's book establishes Proximization Theory firmly as a central methodological and theoretical focus of Critical Discourse Analysis. It provides a coherent framework and exemplary case studies for the analysis of persuasion through intimidation, which go far beyond traditional approaches to this crucial area of public discourse. It is essential reading not just for linguists but also for psychologists and social and political scientists.' - Andreas Musolff, Professor, University of East Anglia, UK This book investigates linguistic strategies of threat construction and fear generation in contemporary public communication, including state political discourse as well as non-governmental, media and institutional discourses. It describes the ways in which the construction of closeness and remoteness can be manipulated in the public sphere and bound up with fear, security and conflict. Featuring a series of case studies in different domains, from presidential speeches to environmental discourse, it demonstrates how political and organizational leaders enforce the imminence of an outside threat to claim legitimization of preventive policies. It reveals that the best legitimization effects are obtained by discursively constructed fear appeals, which ensure quick social mobilization. The scope of the book is of immediate concern in the modern globalized era where borders and distance dissolve and are re-imagined. It will appeal to students and researchers in linguistics, discourse analysis, media communication as well as social and political sciences. Piotr Cap is Professor of Linguistics at the University of Łódź, Poland. His interests are in pragmatics, critical discourse studies, political linguistics and genre theory. His publications include Perspectives in Politics and Discourse (2010),Proximization: The Pragmatics of Symbolic Distance Crossing (2013), Analyzing Genres in Political Communication (2013) andContemporary Critical Discourse Studies (2014). He is Managing Editor of International Review of Pragmatics.
Keywords: Linguistics.; Political communication.; Public policy.; Psycholinguistics.; Discourse analysis.; Political sociology.; elektronické knihy; electronic books